Tezacaftor/Ivacaftor in Subjects with Cystic Fibrosis and F508del / F508del-CFTR or F508del / G551D-CFTR - Donaldson, Scott H.; Pilewski, Joseph M.; Griese, Matthias; Cooke, Jon; Viswanathan, Lakshmi; Tullis, Elizabeth; Davies, Jane C.; Lekstrom-Himes, Julie A.; Wang, Linda T. (American journal of respiratory and critical care medicine, 2018)
Tezacaftor (formerly VX-661) is an investigational small molecule that improves processing and trafficking of the cystic fibrosis transmembrane conductance regulator (CFTR) in vitro, and improves CFTR function alone and in combination with ivacaftor. To evaluate the safety and efficacy of tezacaftor monotherapy and of tezacaftor/ivacaftor combination therapy in subjects with cystic fibrosis homozygous for F508del or compound heterozygous for F508del and G551D. This was a randomized, placebo-controlled, double-blind, multicenter, phase 2 study (NCT01531673). Subjects homozygous for F508del received tezacaftor (10 to 150 mg) every day alone or in combination with ivacaftor (150 mg every 12 h) in a dose escalation phase, as well as in a dosage regimen testing phase. Subjects compound heterozygous for F508del and G551D, taking physician-prescribed ivacaftor, received tezacaftor (100 mg every day). Primary endpoints were safety through Day 56 and change in sweat chloride from baseline through Day 28. Secondary endpoints included change in percent predicted FEV (ppFEV ) from baseline through Day 28 and pharmacokinetics. The incidence of adverse events was similar across treatment arms. Tezacaftor (100 mg every day)/ivacaftor (150 mg every 12 h) resulted in a 6.04 mmol/L decrease in sweat chloride and 3.75 percentage point increase in ppFEV in subjects homozygous for F508del, and a 7.02 mmol/L decrease in sweat chloride and 4.60 percentage point increase in ppFEV in subjects compound heterozygous for F508del and G551D from baseline through Day 28 (P < 0.05 for all). These results support continued clinical development of tezacaftor (100 mg every day) in combination with ivacaftor (150 mg every 12 h) in subjects with cystic fibrosis. Clinical trial registered with www.clinicaltrials.gov (NCT01531673).